LEGAL PROTECTION FOR PARKING SERVICE USERS AGAINST THE APPLICATION OF EXONERATION CLAUSES IN STANDARD AGREEMENTS CONTAINED IN PARKING TICKETS - Helena Valensia; Ivans Januardy; Elin Sudiarti (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This research delves into the asymmetry of rights and obligations between parking operators and consumers arising from the inclusion of exoneration clauses that absolve operators from accountability for vehicle loss or damage. The primary objective of this inquiry is to scrutinize the legitimacy of such clauses through the lens of the principle of contractual autonomy and the Consumer Protection Act, as well as to elucidate their implications for the legal standing of individuals utilizing parking facilities. This research uses a normative legal method and considers both statutory and conceptual approaches to investigate key legal documents such as the Civil Code and Law No. 8 of 1999 regarding Consumer Protection. The findings reveal that exoneration clauses inscribed on parking tickets lack juridical justification, as they contravene Article 18 of the Consumer Protection Law and engender an inequitable contractual relationship between the parties. These clauses weaken the consumer’s position by eliminating the right to compensation and contradict the principle of the deposit agreement, which requires operators to maintain the security of consumers’ vehicles.